COMMUNITY DEVELOPMENT MODEL FOR NATURAL DISASTER SURVIVORS BASED ON PARTICIPATORY PLANNING AND LOCAL WISDOM IN SIRENJA DISTRICT, DONGGALA REGENCY - Hasan Muhamad; Dewi Cahyawati Abdullah; Indah Ahdiah (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Community development, based on social fact conditions, can be an intervention model for social observers who really pay attention to human aspects and community empowerment within it, then this model can be used as an effort to change a community for the better. Ideally, using a participatory approach, this is done because it involves the survivor community from the planning process to decision-making. Therefore, the form of community development that took place during the 2018 Natural Disaster Management did not pay enough attention to this matter. The involvement of communities affected by the 2018 earthquake, liquefaction, and tsunami, which until now still leaves many problems. The problems that arise are mainly caused by economic, socio-cultural backgrounds and differences in livelihoods. This problem can be eliminated if it is planned carefully, takes into account the participatory rural appraisal (PRA) approach, and uses local wisdom in the form of molibu. If this is not done, it is very likely that in the future there will be potential for horizontal conflict. The research method used is a qualitative approach and is equipped with an approach with several study tools and Focus Group Discussions (FGD). Determination of villages affected by the tsunami purposively or deliberately determining 2 (two) villages with the following considerations: 1) Lende Village (as a representation of coastal villages); 2) Sipi Village (the village is in the mountains). The results of the discussion showed that 1) the placement of communities affected by the earthquake, liquefaction, and tsunami was not involved in the placement; 2) ignoring local wisdom; 3) there was a protest movement over their placement, which was considered unfair and the conditions for neopotism; 4) friction occurs in the new community, which has the potential for open conflict.